From the anesthesiologist's perspective retrospective analysis of perioperative complications of transsphenoidal pituitary surgery - (:unkn) unknown (My University, 2006)
Objective: Pituitary surgery presents unique challenges for the anesthesiologist due to the distinct medical co-morbidities associated with various adenomas. The aim of this study was to investigate the perioperative complications throughout the transsphenoidal pituitary surgery from the anesthesiologist's perspective. Methods: Retrospectively, 82 ASA physical status I-II patients, who underwent transsphenoidal surgery between 1st Jan 2002-1st Jan 2006, were included in the study. The following general information was recorded for each patient: demographic data, airway management, cardiovascular and electrocardiographic abnormalities, duration of procedures, pituitary pathology, and any complications during the perioperative period. Results: After induction, four patients developed severe bradycardia and ventricular premature beats with bizarre QRS complex with hypotension, non-responsive to atropine and ephedrine. Three patients experienced intubation problems. In 12 patients, following submucosal injection, a hypertensive response was observed. Only two patients (2.4%) had experienced temporary diabetes mellitus after surgery. Overall, 21 patients (25.6%) experienced complications during the perioperative period of transsphenoidal pituitary surgery. Conclusion: Anesthesiologists must be wary of the possibility of difficult intubation, hypertensive episode at the time of intranasal submucosal injection of vasoconstrictor-supplemented local anesthetic, and hemodynamic and electrocardiographic abnormalities related to the underlying overlooked cardiac pathologies at any time during surgery.
Keywords: Anesthesia; Cardiomyopathy; Complications; Difficult intubation; Transsphenoidal pituitary surgery